Retrospective hospital-based study on snakebite envenomation in Sudan. (8th June 2021) - Khalid, Huda; Azrag, Rasha S
Abstract: Background: Snakebite statistics are lacking in Sudan despite the high estimated burden. In this study we aimed to describe the incidence of snakebite envenomation and death in Sudan and to show the state-wise distribution of snakebite episode. Methods: We retrospectively analyzed hospital-based data on snakebite for 2014–2018. Data were obtained from the annual health statistical reports of the Ministry of Health. Descriptive statistics were used to illustrate the results. Results: A total of 63 160 people were envenomed during 2014–2018 with an average of 12 632 cases/year. The death rate between inpatient cases was 2.5%. The annual incidence was 18– 47 cases/100 000 population. Gadarif state recorded the highest incidence (132/100 000 population) of snakebite envenomation in Sudan whereas Northern state had the least incidence (5/100 000 population). The 15–24 y age group experienced the highest risk of snakebite and males were more exposed to snakebites than females. Conclusions: Although hospital-based records underestimate the burden of snakebite, they can still provide an insight regarding the actual numbers. Here, we highlight the at-risk states in Sudan to be targeted for further questionnaire-based epidemiological studies and to guide health authorities to reduce the burden of snakebite envenomation by insuring proper antivenom distribution to the highly affected areas.